Epistemic distance in Croatian: the case of the l-participle - Stanojević, Mateusz-Milan (2007)
In modern Croatian the l-participle (which is inflected for gender and number) is used to form the perfect tense, the pluperfect tense, the ?second future? tense, the first and second conditional, and the optative. Croatian grammars (e.g. Barić, E. et al. 1995 ; Katičić 1991 ; Silić and Pranjković 2005) describe their formation and use, but they do not provide any explanations of the possible reasons behind them. The aim of this paper is to provide a unified account of all the usages of the l-participle in Croatian, which we claim express epistemic distance, i.e. the distance of the process in relation to the speaker and her knowledge about the event (Langacker 1991). This is most readily visible in the two conditionals, the second future and the optative. Here is an example of the first conditional: (1) One bi se bavile They be-PERF-AORIST-3rd ?pl. refl deal-IMPERF-PARTICIPLE-pl-fem točno određenim pitanjima exactly defined issues ?They would deal with very specific issues?. This expresses conditional action which might happen, but the speaker is uncertain whether it in fact will. Similarly, the second future appears only in dependent (usually temporal and conditional) clauses, as in (2) Ako ga budeš sreo, If him be-PERF-PRES-2nd-sg meet-PERF-PARTICIPLE-sg-masc pozdravi ga. greet-PERF-PRES-2nd-sg him ?If you see him, give him my best.? Example (2) signifies that the action of meeting the person may happen, but is not certain. However, epistemic distance is not so apparent in examples of the perfect tense, which is the most widely used l-participle construction. Here is an example: (3) Stigao sam iz Arrive-PERF-PARTICIPLE-sg-masc be-IMPERF-PRES-1st-sg from daleka. far ?I have arrived/arrived from far away.? The problem with (3) is that it is sometimes claimed to refer to an action that has ramifications for the present (which would go against the epistemic distance interpretation) in addition to a general past action with no current relevance. A cognitive analysis has shown that the perfect is vague as to current relevance (Stanojević and Geld 2005), and that current relevance primarily appears with perfective verbs (Geld and Stanojević 2005). In this paper we will be building on the points about the perfect made there, reinforcing them on the basis of two corpus studies. In the first one, we have selected six most frequent Croatian perfective verbs (doći ?come?, otići ?leave?, reći ?say?, vidjeti ?see?, dobiti ?get? and kupiti ?buy? ; frequency established based on a frequency dictionary of Croatian (Moguš, Bratanić and Tadić 1999)). We used recent non-fictional texts from the Croatian National Corpus (www.hnk2.ffzg.hr) to identify their patterns of usage in the perfect tense. This study showed that the perfect is in fact most frequently used in non-currently relevant contexts. In the second corpus study, we analyze the patterns of usage of all the l-participles in the (newspaper) subcorpus (cw2000) of the Croatian National Corpus, which allows search by a particular form. Several factors will be taken into consideration: verbal aspect, its interplay with particular constructions, and time adverbials used with the perfect. Preliminary results suggest the predominance of the perfect tense and its primary use in non-currently relevant contexts. Based on our previous work, the two studies and some diachronic and cross-linguistic evidence, we will attempt to provide a schematic characterization of the l-participle in Croatian, relying on the notion of epistemic distance combined with the notion of an epistemically distant virtual plane (V2). If the distinction between an epistemically immediate V1 and epistemically distant V2 proves viable, it may have significant consequences for the analysis of other languages. References Barić, E. et al. 1995. Hrvatska gramatika. Zagreb: Školska knjiga Geld, R. and Stanojević, M. M. 2005. Current relevance in the Croatian perfekt tense: speaker?s cognitive space?. Paper presented at the 9th International Cognitive Linguistics Conference. Language, Mind and Brain. Yonsei University, Seoul, Korea, July 17-22, 2005 Katičić, R. 1991. Sintaksa hrvatskoga književnog jezika. Zagreb: Hrvatska akademija znanosti i umjetnosti Langacker, R. 1991. Foundations of Cognitive Grammar. Vol. 2. Descriptive Application. Stanford: Stanford University Press Moguš, M., Bratanić, M and Tadić, M. 1999. Hrvatski čestotni rječnik. Zagreb: Školska knjiga Silić, J. and Pranjković, I. 2005. Gramatika hrvatskoga jezika za gimnazije i visoka učilišta. Zagreb: Školska knjiga Stanojević, M.-M. and R. Geld. 2005. Current relevance: a cognitive account. Glossos 6. http://www.seelrc.org/glossos/issues/6/stanojevic.pdf